О необходимости модификации зависимости между расстоянием поражения и пиковым током молнии, рекомендуемой Европейским стандартом EN 62305-1:2006 - Стружевски, П. (Технічна електродинаміка, 2011)
In the article it has been shown that existing European Standard EN 62305-1:2006 does not represent accurately the relation between striking distance and peak current of atmospheric discharge in electrogeometric numerical models of lightning selectivity estimation. The author has stressed that this relation was obtained using faulty distribution of lightning current amplitude AIEE. He has analyzed its divergence with other distributions of this parameter that are used at present. The author has also proposed to introduce the justified correction into the mentioned above standardized function and into other similar relations.